Rh D genotyping in pregnancy-present and future - Velkova, Emilija; Makarovska Bojadzieva, Tatjana; Hristova Dimcheva, Anita; Dejanova-Ilijevska, Violeta; Petkovikj, Elena; Ristovska, Elena (ECronicon Open Access, 2021)
Background: The RBC’s (Red Blood Cell’s) antigen can cause alloimmunisation during pregnancy if the fetus inherited the antigen from the father that is not present in the mother. In most of the cases the RBS’s antibody are from IgG class and they cross the placental barrier, binding the Fc receptors as an active one way transport from the mother to the fetus and never cross versa. Aim: To emphasize that methods of genotyping in pregnancy improve the management of sensibilised pregnancies in high risk of HDFN easier and safer minimising the unnecessary procedure. Prove that with genotyping antenatal use of RhIG can be reduced, same as use of RhD-negative blood for transfusion. Materials and Methods: All pregnant women were tested for ABO, RhD, Rh phenotype, K and screening of alloantibodies in the first trimester of pregnancy. Pregnant women who have the DVI phenotype are typed as D-negative. Pregnant women, 50 in total, with weak expression of D, with score < 2+, including those with DEL phenotype, were tested with a panel of D monoclonal antibodies, commercial kit, or by molecular testing, for RhD variants. Results: The results that we have obtained show that 17 samples were RhD-negative and 33 samples showed results for weak D: weak D Type 1 (60,6%), Type 2 (12,2%), Type 3 (24,2%) and only 1 pregnant woman was RhD Type 4. The research also included 30 pregnant women where the RhD fetal status had been detected by non-invasive technique from the mother’s plasma, by Real time PCR method, between the 12 and 31 gestation week. Acquired results demonstrated that 12 fetuses were female, 16 were male and 3 fetuses were without specified sex. Conclusion: In our study only 3% of RhD-negative mothers needed RhIG prophylaxis, and 97% were weak D variants 1 - 3 that we can consider as RhD-positive and they didn’t need an RhIG prophylaxis, subsequently they can be transfused with RhD-positive blood. According to the results, we provide RhIG antenatal prophylaxis in 97% unnecessarily and expose the women on human product, with all risk of it. Also, there is a possibility to save a stock of RhD-negative blood in these women, if the transfusion is necessary.
Keywords: RBC’s (Red Blood Cell’s); Rh D Genotyping; Pregnancy